Virtual Reality-Assisted Cognitive Behavioral Therapy for Anxiety Disorders: A Systematic Review and Meta-Analysis - Wu, Jinlong; Sun, Yi; Zhang, Gongwei; Zhou, Zhenhui; Ren, Zhanbing (Frontiers in Psychiatry, 2021)
Abstract Objective: To explore the effectiveness of virtual reality-assisted cognitive behavioral therapy (VRCBT) in the treatment of anxiety and depression in patients with anxiety disorders. We further compare the therapeutic effect of VRCBT with that of standard cognitive behavioral therapy (CBT), as well as investigate the long-term efficacy of VRCBT. Methods: As of March 3, 2020, a total of 4 databases (Web of Science, PubMed, PsycINFO, and Scopus) were retrieved, and two researchers independently conducted literature retrieval and research selection and performed data extraction. Methodological quality assessment was performed using the Cochrane risk of bias tool and Grading of Recommendation, Assessment, Development, and Evaluation tool (GRADE). Results: Meta-analysis showed that the therapeutic effect of VRCBT on anxiety was better than that of the waiting list group (WLG) (SMD = −0.92; 95% CI: −1.34, −0.50; P = 0.005, I2 = 66%, n = 276), while the therapeutic effect of VRCBT on anxiety was similar to that of standard CBT treatment (SMD = −0.26; 95% CI: −0.50, −0.01; P = 0.77, I2 = 0%, n = 150). We further found that the therapeutic effect of VRCBT on depression was better than that of the WLG (SMD = −1.29; 95% CI: −2.26, −0.32; P = 0.09, I2 = 58%, n = 74), while the effect of VRCBT was similar to that of standard CBT (SMD = −0.30; 95% CI: −0.67, −0.07; P = 0.39, I2 = 1%, n = 116). Of the five studies that reported withdrawal rates of patients during the VRCBT and CBT treatment process, the withdrawal rates of VRCBT group and CBT group did not reach statistical significance (OR = 0.70, 1.48, P > 0.05); only two studies reported the long-term effectiveness of VRCBT in anxiety and depression on patients with anxiety disorders. Conclusion: VRCBT treatment has a specific positive effect on patients with anxiety disorders (anxiety, depression). Compared with standard CBT, similar therapeutic effects can be achieved in the treatment of anxiety disorders.